Flow field analysis of micro particles passing through pervious concrete. (March 2019) - Nan, Xuan; Zhang, Mingfei; Liu, Yanhui; Wang, Jing; Wang, Lina; Jing, Ling
Abstract: In order to study the pore seepage and clogging problems in the permeable concrete, the permeable concrete blockage test device was used to simulate the flow law and distribution of the surface micro-particles through the concrete at the beginning of rainfall. The internal pore structure was reconstructed by CT scanning technique combined with avizo software. The DPM model in CFD was used to simulate the multiphase flow of Kunming surface microparticles through the permeable concrete. The results show: The results obtained by CFD numerical simulation are in good agreement with the experiment. The surface micro-particles with particle size range of 200-500um have a certain degree of blockage to concrete, and still have good water permeability (higher permeability coefficient), and after adding below 200um The particle clogging is more significant, and the permeability coefficient is basically close to 0; but more importantly, it is found by DPM simulation that the small particles of 0-100 um pass through the concrete and the seepage velocity is slow and the partial adhesion to the wall of the tunnel causes the diameter to decrease and affect the seepage.